Is thyroid stimulating hormone titration mandatory in the routine work-up of African males from infertile couples? - Ngowa, Jean D. Kemfang; Tchawe, Yvan S. Ngaha; Voundi, Esther V.; Toukam, Michel; Ngassam, Anny; Noa, Cyrille C.; Nshalai, Christiane; Metogo, Junie; Sobngwi, Eugene (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The impact of thyroid hormones on male reproductive function is still insufficiently understood. The objectives of this study were to determine the frequency of thyroid dysfunction in men from infertile couples and to establish an association between TSH (thyroid stimulating hormone) values and sperm parameters. Methods: We conducted a cross-sectional analytical study on a consecutive series of men managed for couple infertility in two reference hospitals of Yaoundé from November 2017 to May 2018. For each participant, a questionnaire was administered, TSH was assayed using electro-chemo-luminescence and sperm analyzed. Statistical methods used were the Mann-Whitney test and the Spearman correlation coefficient with a significance threshold of 5%. Results: Overall, 123 men were recruited. The median age was 44 years old [38-50 years]; 60 (48.79%) patients had couple infertility lasting between 1 and 5 years. Primary infertility of the couple was the most common (82 cases, 66.70%). After sperm analysis, 86 patients (70%) had one or more anomalies. TSH titration revealed 03 (2.44%) cases of subclinical hyperthyroidism, 05 (4.06%) subclinical hypothyroidism and 115 (93.50%) euthyroidism. Significant associations were found between TSH and sperm parameters in the group of patients with thyroid dysfunction, but none in the euthyroid group. Conclusions: Frequency of dysthyroidism is low among African males from infertile couples. We noted significant correlations between TSH values and sperm parameters. The low frequency of thyroid dysfunction would be against a TSH titration in the routine work-up of these patients.